2022
DOI: 10.4018/ijwsr.299017
|View full text |Cite
|
Sign up to set email alerts
|

(Offloading) QoE-Aware Application Mapping and Energy-Aware Module Placement in Fog Computing + Offloading

Abstract: Fog computing is a potential solution for the Internet of Things in close connection with things and end-users. Fog computing will easily transfer sensitive data without delaying distributed devices. Moreover, fog computing is more in real-time streaming applications, sensor networks, IoT which need high speed and reliable internet connectivity. Due to the heterogeneous and distributed characteristics, finley distributing the task with computation offloading is a challenging task. Developing an efficient QoE-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In [ 20 ], the authors suggested a method for placing incoming modules onto Fog devices that takes into account Quality of Experience (QoE) and energy efficiency. This involves using Fuzzy logic-based approaches and a multi-constraint single objective optimization technique for QoE-aware application mapping.…”
Section: Related Workmentioning
confidence: 99%
“…In [ 20 ], the authors suggested a method for placing incoming modules onto Fog devices that takes into account Quality of Experience (QoE) and energy efficiency. This involves using Fuzzy logic-based approaches and a multi-constraint single objective optimization technique for QoE-aware application mapping.…”
Section: Related Workmentioning
confidence: 99%
“…Many research studies have tried to address the placement problem from various perspectives. Some have considered minimising the overall application latency [12,[15][16][17][18] while placing the application modules on fog nodes, whereas some research has considered the energy consumption [19][20][21] of the fog nodes while placing the application modules. Despite the efforts in the previous research, there's a need for more robust solutions that take into account both latency, energy consumption, and the completion time of the applications.…”
Section: Introductionmentioning
confidence: 99%
“…Partial offloading efficiently utilizes both the local and MEC resources. With good splitting of a task between local processing and MEC offloading, partial offloading can efficiently minimize the task execution time, and it is a promising technique for the IoT [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%